DINAMIKA KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA KUPANG - Sofiany Hillarry Wua Rumat; Norman Duma Sitinjak (University of Merdeka Malang, 2019)
Research on taxpayer compliance continues because it is very important especially for the government. The state concern to individual taxpayers because more people have taxable income. This study examines the compliance of individual taxpayers, namely government employees who live in the Kupang City. The findings in this study are the willingness to pay taxes significantly influence individual taxpayer compliance. The reason is the tax owed by government employees in an orderly manner is cut directly by the government treasurer.